2012
DOI: 10.1136/bmjopen-2012-001117
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the new rheumatoid arthritis 2010 ACR/EULAR classification criteria in routine clinical care

Abstract: ObjectivesThe new 2010 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) criteria for rheumatoid arthritis (RA) have been designed to classify early onset RA, but has not been studied to identify RA in patients with arthritis seen in routine clinical care where correct ‘classification’ of patients, when they are not selected for having RA would be important.DesignProspective, consecutive patients cohort.SettingOutpatient clinic of a university rheumatology centre.ParticipantsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…The 2010 criteria as applied in this group of patients had a poorer positive predictive value (44 vs. 61%) and a similar negative predictive value (98 vs. 97%) to the 1987 criteria. The authors believe that their study [11], performed in routine daily care, showed that the criteria have low specificity, and therefore incorrectly labels patients as having RA.…”
Section: Performance Of the New Criteriamentioning
confidence: 92%
See 1 more Smart Citation
“…The 2010 criteria as applied in this group of patients had a poorer positive predictive value (44 vs. 61%) and a similar negative predictive value (98 vs. 97%) to the 1987 criteria. The authors believe that their study [11], performed in routine daily care, showed that the criteria have low specificity, and therefore incorrectly labels patients as having RA.…”
Section: Performance Of the New Criteriamentioning
confidence: 92%
“…However, these patients have lower disease activity at initial presentation [10 & ]. A more critical publication by Kennish et al [11] studied the value of the new criteria in a prospective consecutive patients cohort of 126 patients with joint symptoms. Both the 2010 ACR/EULAR RA criteria and the 1987 RA criteria were applied and the gold standard for the diagnosis of RA was the primary rheumatologist's diagnosis.…”
Section: Performance Of the New Criteriamentioning
confidence: 98%
“…A study flow diagram showing these articles is shown in Figure 1. [16] Description of the studies These 10 studies included cohorts from the Netherlands, [6][7][8] the United States, [13] France, [10] UK, [9] New Zealand, [14] Spain, [15] South Korea, [11] and Japan. [6,12] The three studies [6][7][8] from the Netherlands used different cohort databases: the Rotterdam Early Arthritis Cohort" (REACH), the Stop Arthritis Very Early (SAVE) trial, and the Leiden early arthritis clinic (EAC) cohort).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Seven studies [7,[9][10][11][12]14,15] were included in the DMARD group with a sensitivity between 0.34 and 0.86, and a specificity between 0.40 and 0.78. The expert opinion group (expert group for short) was composed of five studies, [7,8,10,13,15] be defined within the same model which provides a general framework for the meta-analysis of diagnostic test studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation